1981
DOI: 10.3382/ps.0601807
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Heart, Liver, and Skeletal Muscle from Broilers with Coccidiosis

Abstract: Infection with Eimeria acervulina, Eimeria brunetti, or Eimeria tenella affected the composition of the breast, thigh, heart, and liver of 3 or 4-week-old broilers. Liver glycogen was significantly increased at 6 and 8 days postinoculation (PI) with E. acervulina. Conversely, liver glycogen was decreased at 4 and 6 days PI with E. tenella and was unaffected by infection with E. brunetti. The levels of RNA and lipid in the liver were decreased with E. acervulina but unchanged with E. tenella. Both species decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
6
1
2
Order By: Relevance
“…Isso ocorreu, possivelmente, devido a uma alteração no metabolismo de lipídio hepático decorrente das lesões intestinais resultantes do ciclo evolutivo do parasito. Todas as lesões decorrentes da reprodução parasitária interferem diretamente a absorção de nutrientes, desencadeando uma série de distúrbios no metabolismo de carboidratos (FREEMAN, 1970;ALLEN;MCMURTRY, 1984), proteínas (RUFF et al, 1981;FETTERER;ALLEN, 2000), lipídeos (ALLEN, 1988) e macro e micro-minerais (TURK, 1986ab). Na presente pesquisa, as doses de 1x10 6 e 1x10 5 oocistos de E. acervulina inoculadas nos grupos A e B, respectivamente, foram suficientes para ocasionar sérios danos ao organismo animal, porém o grupo A foi o mais afetado pela infecção, ficando evidente que a intensidade das alterações clinicas e patológicas é decorrente da dose infectante.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Isso ocorreu, possivelmente, devido a uma alteração no metabolismo de lipídio hepático decorrente das lesões intestinais resultantes do ciclo evolutivo do parasito. Todas as lesões decorrentes da reprodução parasitária interferem diretamente a absorção de nutrientes, desencadeando uma série de distúrbios no metabolismo de carboidratos (FREEMAN, 1970;ALLEN;MCMURTRY, 1984), proteínas (RUFF et al, 1981;FETTERER;ALLEN, 2000), lipídeos (ALLEN, 1988) e macro e micro-minerais (TURK, 1986ab). Na presente pesquisa, as doses de 1x10 6 e 1x10 5 oocistos de E. acervulina inoculadas nos grupos A e B, respectivamente, foram suficientes para ocasionar sérios danos ao organismo animal, porém o grupo A foi o mais afetado pela infecção, ficando evidente que a intensidade das alterações clinicas e patológicas é decorrente da dose infectante.…”
Section: Discussionunclassified
“…De acordo com Morehouse e Mcguire (1958), o parasita invade as células epiteliais do duodeno, onde a infecção é mais severa, e avança até a parte média do intestino delgado causando destruição epitelial e conseqüente enterite. Segundo Terra et al (2001) as lesões provocadas no epitélio intestinal, resultantes das fases de desenvolvimento, prejudicam os índices zootécnicos dos frangos e, conseqüentemen-te, o resultado econômico da empresa avícola.…”
unclassified
“…Liver glycogen in growing Leghorn chicks was 2.46 mg /100 mg of liver dry weight (Sarkar, 1971 and1973). In another study liver glycogen content in broiler chicks at a comparable age was found to be 2.92 mg/100 mg of liver dry weight (Ruff et al, 1981).…”
Section: Introductionmentioning
confidence: 87%
“…Liver storage of fat and glycogen as well as plasma lipids profile may reflect energy homeostasis and lipids mobilization in the body. Ruff et al, (1981) stated that fat content in liver of broilers at 4 weeks of age was found to be 17.3 % based of liver dry weight. However, Patel et al (1981) reviewed that content of liver fat of White Leghorn chicks at 8 weeks of age was 13.2 % based of liver dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations in this laboratory have focused upon the effects that coccidial infections have on liver glycogen stores (Ruff et al, 1981;Ruff and Allen, 1982). Because Eimeria acervulina infections can cause marked elevations of glycogen levels at 7 to 8 days after inoculation (DAI) (Ruff and Allen, 1982), it was conjectured that infections might be associated with abnormal changes in levels of pancreatic hormones.…”
Section: Introductionmentioning
confidence: 99%